Functional Analysis of DNMT1 SNPs (rs2228611 and rs2114724) Associated with Schizophrenia - Sonal Saxena; Pranay Amruth Maroju; Sumana Choudhury; Vidhya Chitta Voina; Poonam Naik; Kavitha Gowdhaman; Poornima Kkani; Kiranmai Chennoju; S. Ganesh Kumar; C. Ramasubramanian; G. Prasad Rao; Trinath Jamma; et al. (Genetics Research)
A recent study showed the association of minor alleles of rs2228611 (T allele) and rs2114724 (T allele) of DNMT1 with schizophrenia (SZ) and suggested their effects on splicing of the transcripts. We performed a replication study using 310 controls and 304 SZ patients and confirmed the association of the homozygous minor allele genotypes with SZ (P = 0.04 for rs2114724 and P = 0.007 for rs2228611). This significant association persisted after Bonferroni correction when the previously published data of 301 controls and 325 patients were also considered (P ≤ 0.0002). In addition, we found that the proportion of male patients with homozygous minor alleles at rs2114724 was significantly higher than that of females (P = 0.002). When haplotype analysis of both loci was performed, we observed a significant association of T/T–T/T and T/T–C/T (P = 0.04) haplotypes with SZ. To gain insights into the functional effects of the two SNPs on the levels of DNMT1 transcripts, quantitative real-time PCR experiments were performed using peripheral blood monocytes from 10 individuals each with T/T–T/T (homozygous minor allele), C/T–C/T (heterozygous), and C/C–C/C (homozygous major allele) haplotypes. Independently, the levels of DNMT1 protein were also compared in three individuals each by immunofluorescence. These results suggest that neither DNMT1 transcript nor the protein levels were significantly different in the peripheral blood monocytes among the individuals studied for the three groups. Taken together, our results confirm that the two minor alleles in homozygosity are associated with SZ but with no discernible effects on transcript or protein levels of DNMT1 in the peripheral blood monocytes of the small number of samples tested.